Dynamic and Geological-Ecological Spatial Planning Approach in Hot Mud Volcano Affected Area in Porong-Sidoarjo - Haryo Sulistyarso (IPTEK The Journal for Technology and Science, 2010)
By May 29t h 2006 with an average hot mud volcano volume of 100,000 m3 /per day, disasters on well kick (i.e. Lapindo Brantas Ltd.) in Banjar Panji 1 drilling well have deviated the Spatial Planning of Sidoarjo’s Regency for 2003- 2013. Regional Development Concept that is aimed at developing triangle growth pole model on SIBORIAN (SIdoarjo-JaBOn-KRIaAN) could not be implemented. This planning cannot be applied due to environmental imbalance to sub district of Porong that was damaged by hot mud volcano. In order to anticipate deviations of the Regional and Spatial Planning of Sidoarjo Regency for 2003-2013, a review on regional planning and dynamic implementation as well as Spatial Planning Concept based on geologicalecological condition are required, especially the regions affected by well kick disaster. The spatial analysis is based on the geological and ecological condition by using an overlay technique using several maps of hot mud volcano affected areas. In this case, dynamic implementation is formulated to the responsiblity plan that can happen at any time because of uncertain ending of the hot mud volcano eruption disaster in Porong. The hot mud volcano affected areas in the Sidoarjo’s Spatial Planning 2009-2029 have been decided as a geologic protected zone. The result of this research is scenarios of spatial planning for the affected area (short term, medium term and long term spatial planning scenarios).